Rolnicza Polska w Unii Europejskiej - Kapusta, Franciszek (Agricultural Poland in the European Union (25), 2008)
Polish agriculture is in the process of double transformation: a) from centrally planned into free market economy - open within the EU b) process of application of legal framework of the EU but at the significantly weaker terms of support for direct subsidies. In every country agriculture plays in the countryside a special role, which is formed by history and the specificity of applied production factors. Agriculture, while developing production, creates natural environment, which has significant impact on life of whole society. Regardless of that function, agriculture has to secure society of the given country in sufficient amount of production and form the basis of national food safety and food sustainability. Polish agriculture fits into existing structers of agriculture of 'old' EU with many problems. Generally speaking, products of Polish agriculture entered the EU market and gained very good position, mainly thans to good quality (flavour, ingredients) and competitive price. Poland moved from position of net importer into - increasingly from year to year - net exporter. It has to be noted that once achieved position is not eternal and requires new solutions in order to keep it and even improve it.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 313-327